Positive electrode active material and lithium secondary battery including the same
By controlling the reaction conditions to induce uniform particle growth within secondary particles, the method addresses the structural and performance issues of Ni-based cathode active materials, resulting in a stable, high-capacity positive electrode material for lithium secondary batteries.
Patent Information
- Application Number
- JP2024092319
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-07
- Filing Date
- 2024-06-06
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional Ni-based layered cathode active materials for lithium secondary batteries suffer from performance deterioration due to micro-cracks, structural instability, and atomic/nanoscale defects, limiting their cycling properties and structural stability, which hinders their commercial application.
A method involving a three-step process: mixing a metal hydroxide and a lithium precursor, heat-treating the precursor mixture, and sintering it to form LMO x, controlling the reaction temperature and inducing uniform growth of primary particles within secondary particles, thereby minimizing atomic and nanoscale defects.
The method enables the synthesis of a high-capacity, stable positive electrode active material in a single step without additional additives, enhancing the battery's long-term performance and suitability for various industrial applications.
Smart Images

Figure 2024177126000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same, and more particularly, to a positive electrode active material and a lithium secondary battery including the same that can induce uniform particle growth of primary particles in secondary particles in a relatively simple process without additional additives or process design, and can ensure stability and exhibit excellent electrochemical properties by controlling atomic and nanoscale defects. [Background technology]
[0002] Lithium secondary batteries are used in various fields such as mobile devices, energy storage systems, electric vehicles, etc., due to their high energy density and voltage, long cycle life, and low self-discharge rate. The core materials of such lithium secondary batteries are the positive electrode material, the negative electrode material, the electrolyte, and the separator. Recently, with the increasing demand for electric vehicles, the importance of the positive electrode active material of lithium secondary batteries to drive them is becoming more and more apparent.
[0003] The positive electrode active material can be classified into LCO (lithium cobalt oxide), NCM (lithium nickel cobalt manganese oxide), NCA (lithium nickel cobalt aluminum oxide), LMO (lithium manganese oxide), LFP (lithium iron phosphate), etc. according to the constituent material. LiNi x Co y Mn z O2 and LiNi x Co y Al z Ni-based layered positive electrode active materials such as O2 are mainly used. The Ni-based layered positive electrode active materials reduce costs by replacing a portion of the expensive cobalt with nickel, and have the advantages of high energy density and relatively long life, and can increase the reversible capacity of lithium secondary batteries.
[0004] However, despite the excellent electrical / chemical properties of such Ni-based layered positive electrode active materials, their commercial application is limited by the following problems, such as limitations in cycling characteristics or structural stability.
[0005] First, conventional Ni-based layered positive electrode active materials are manufactured by mixing a lithium source with a precursor synthesized by coprecipitation and then synthesizing it in a solid phase, but in this case, there is a problem of deterioration in the performance of lithium secondary batteries due to micro-cracks. More specifically, Ni-based layered positive electrode active materials generally have a secondary particle structure of several μm in size, in which fine primary particles of submicron size are aggregated, but in the case of Ni-based layered positive electrode active materials synthesized by the conventional coprecipitation method, micro-cracks are generated inside the secondary particles during long-term charge / discharge processes, causing new interface exposure and accelerating side reactions with the electrolyte at the interface, which can cause deterioration in battery life characteristics.
[0006] Secondly, to fully utilize the excellent electrical / chemical properties of the Ni-based layered positive electrode active material and realize high energy density, an increase in electrode density (>3.3g / cc) is required, but in the case of Ni-based positive electrode active material synthesized by the conventional co-precipitation method, the secondary particles have low structural stability as described above, so the secondary particles easily collapse, which leads to a problem of electrolyte depletion due to a side reaction with the electrolyte. In other words, the Ni-based layered positive electrode active material in the form of secondary particles synthesized by the existing co-precipitation method has limitations in terms of showing high energy density properties.
[0007] Third, Ni-based layered positive electrode active materials can cause a decrease in battery performance, such as a decrease in capacity, due to the instability of highly oxidized Ni cations and oxygen desorption from the host structure. That is, oxygen desorption can cause an excess of NiO with a rock salt structure to form in the layered structure of the positive electrode active material, which can increase Li by-products. In this case, NiO gradually increases with repeated charging and discharging, increasing resistance, and various side reactions can occur as the Li by-products increase, which can result in deterioration of battery performance, such as a decrease in capacity.
[0008] In this way, atomic-scale defects such as oxygen evolution and cation mixing that appear in conventional synthesis processes can lead to nano-level defects such as nanopores, which exist in a variety of sizes, from voids within particles to voids between particles, and are factors that hinder the achievement of high capacity and stabilization of Ni-based layered positive electrode active materials.
[0009] As a result, Ni-based layered positive electrode active materials are attracting attention as potential positive electrode materials because they can exhibit high energy density and increased life span. In order to fully utilize the excellent electrical and chemical properties of these materials, there is an urgent need for research that can control atomic and nanoscale defects by inducing particle growth through uniform reactions of primary particles within the secondary particles that make up the Ni-based layered positive electrode active materials. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Korean Patent Publication No. 2016-0094063 (2016.08.09) Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention is made to overcome the above-described problems, and the problem to be solved by the present invention is that after the pretreatment proceeds at the temperature at which the metal hydroxide and the lithium precursor start to react, by finally synthesizing, particle growth due to uniform reaction of primary particles in secondary particles can be induced to control nanoscale defects, and a cathode active material capable of solving the problem of performance deterioration with a long life and a method for manufacturing the same are provided.
[0012] Furthermore, another problem to be solved by the present invention is that it can be synthesized in a single synthesis step without a special additive, there is no need to change the existing process design, and by synthesizing a cathode active material with improved performance compared to the existing one, a high added-value cathode active material for a lithium secondary battery that can be utilized in various industrial groups and a method for manufacturing the same are provided.
Means for Solving the Problems
[0013] In order to solve the above-described problems, the present invention includes a first step of mixing a metal hydroxide and a lithium precursor to form a precursor mixture, a second step of heat-treating the precursor mixture, and sintering the heat-treated precursor mixture to produce LMO x and a third step of manufacturing the same, and provides a method for manufacturing a cathode active material. At this time, L is Li (lithium), M is one or more selected from Co (cobalt), Ni (nickel), Al (aluminum), Mn (manganese), and Mg (magnesium), and x is a constant of 0.5 to 2.5.
[0014] Further, according to an embodiment of the present invention, the LMO x can be characterized in that it is a compound represented by the following Chemical Formula 1.
Chemical Formula
[0015] The first-stage lithium precursor further includes a molten salt.
[0016] In addition, the intermediate phase represented by the following Chemical Formula 2 is formed through the second heat treatment, and the primary particles in the secondary particles grow uniformly. [ka] In this case, M is one or more selected from Co (cobalt), Ni (nickel), Al (aluminum), Mn (manganese) and Mg (magnesium), and x is a constant of 0.2 to 0.8.
[0017] The second heat treatment is performed at 200 to 400° C. for 2 to 8 hours.
[0018] The metal hydroxide and the lithium precursor in the first step are mixed in a molar ratio of 1:0.9 to 1.1.
[0019] The third step is characterized in that it is carried out at 600 to 900° C. for 6 to 16 hours.
[0020] The molten salt is at least one selected from the group consisting of LiNO3, Li2SO4, Li2CO3, LiCl, LiI, and LiBr.
[0021] The lithium precursor is characterized in that either one of LiOH or LiOH·H2O and the molten salt are mixed in a ratio of 1:0.5 to 2.
[0022] The intermediate phase is contained in an amount of 40 to 80% by weight based on the total weight of the precursor mixture.
[0023] Furthermore, the present invention provides a positive electrode active material in the form of secondary particles with minimized atomic units and nanoscale defects, which is represented by Chemical Formula 3 below and includes a first void formed between particles having an average radius of less than 960 Å and a second void formed within particles having an average radius of less than 80 Å.
Chemical Formula
[0024] Moreover, according to one embodiment of the present invention, the positive electrode active material is characterized by being a compound represented by Chemical Formula 4 below.
Chemical Formula
[0025] In addition, the first void is characterized by having a distribution of less than 0.012 cm 3 / g.
[0026] Also, the second void is characterized by having a distribution of less than 0.0009 cm 3 / g.
[0027] Furthermore, the present invention provides a lithium secondary battery including the above-described positive electrode active material.
Advantages of the Invention
[0028] The present invention can induce particle growth due to a uniform reaction of primary particles within secondary particles constituting a positive electrode active material, thereby controlling nanoscale defects, solving the problem of performance degradation over a long life span, and easily synthesizing a positive electrode active material having high capacity in a single synthesis process while ensuring stability without the need for special additives, thereby greatly improving the applicability to various industries in which lithium secondary batteries are used. [Brief description of the drawings]
[0029] [Figure 1] This is an SEM image of a cross section of secondary particles after 150 cycles for a conventional Ni-based layered positive electrode active material. [Diagram 2] 1 is a SEM image showing a cross section of a secondary particle of a Ni-based layered positive electrode active material according to the present invention after 150 cycles. [Diagram 3] 1 is an image showing a thermogravimetric analysis result of a positive electrode active material precursor mixture according to an embodiment of the present invention. [Figure 4a] 1 is a graph showing a phase fraction of an intermediate phase through Rietveld analysis of an X-ray diffraction (XRD) pattern of a positive electrode active material according to an embodiment of the present invention. [Figure 4b] 1 is a graph showing the results of Rietveld analysis of a neutron diffraction pattern of an intermediate phase of a positive electrode active material according to an embodiment of the present invention. [Diagram 5] 4 is a graph showing a phase fraction analysis result of an intermediate product during sintering of a positive electrode active material according to an embodiment of the present invention. [Figure 6] 1 is a graph showing an analysis of changes in phase fraction and lattice constant during primary sintering of a positive electrode active material according to an embodiment of the present invention. [Figure 7] 1 is a graph showing the results of an XAS analysis that can confirm the particle growth uniformity of secondary particles before / after primary sintering of a positive electrode active material according to an embodiment of the present invention. [Figure 8] 1 is an image and a graph showing the results of a XANES analysis and a transmission electron microscope (TEM) analysis of a positive electrode active material according to an embodiment of the present invention. [Figure 9]1 is a graph showing the results of XRD and ND pattern analysis of an intermediate phase of a positive electrode active material according to one embodiment of the present invention. [Figure 10] 1 shows a cross-sectional SEM image of a particle of a positive electrode active material according to an embodiment of the present invention. [Figure 11] 1 shows a cross-sectional SEM image of a particle of a positive electrode active material according to an embodiment of the present invention. [Figure 12] 1 is a graph showing the results of SAXS and SANS analysis of a positive electrode active material according to one embodiment of the present invention. [Figure 13] 1 is a graph showing the results of SAXS and SANS analysis of a positive electrode active material according to one embodiment of the present invention. [Figure 14] 1 is a graph showing the results of SAXS and SANS analysis of a positive electrode active material according to one embodiment of the present invention. [Figure 15] 1 shows XRD and ND pattern analysis, SAXS and SANS analysis, and TEM and SEM cross section of a positive electrode active material according to one embodiment of the present invention. [Figure 16] 1 shows XRD and ND pattern analysis, SAXS and SANS analysis, and TEM and SEM cross section of a positive electrode active material according to one embodiment of the present invention. [Figure 17] 1 shows XRD and ND pattern analysis, SAXS and SANS analysis, and TEM and SEM cross section of a positive electrode active material according to one embodiment of the present invention. [Figure 18] 1 shows XRD and ND pattern analysis, SAXS and SANS analysis, and TEM and SEM cross section of a positive electrode active material according to one embodiment of the present invention. [Figure 19] 1 shows XRD and ND pattern analysis, SAXS and SANS analysis, and TEM and SEM cross section of a positive electrode active material according to one embodiment of the present invention. [Figure 20] 1 is a graph showing the electrochemical performance of a positive electrode active material according to an embodiment of the present invention. [Figure 21] 1 is a graph showing electrochemical performance of a positive electrode active material according to another embodiment of the present invention. [Figure 22] 1 is a graph showing electrochemical performance of a positive electrode active material according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention may, however, be embodied in various different forms and should not be construed as being limited to the embodiments set forth herein.
[0031] As mentioned above, the material with the highest capacity among the existing layered positive electrode active materials is a high-nickel layered positive electrode active material, but due to the instability of nickel cations, it is difficult to synthesize stoichiometric materials, and there are problems with the formation of atomic-scale defects such as oxygen generation and cation mixing during the synthesis process. In addition, atomic-scale defects lead to nano-level defects such as nanopores, and these nano-level defects exist in various sizes, from voids within particles to voids between particles, and cause deterioration of life characteristics. In other words, there are limitations to commercialization due to limitations in cycling characteristics or structural stability.
[0032] Thus, the present invention provides a method for producing a LMO by a first step of mixing a metal hydroxide and a lithium precursor to form a precursor mixture, a second step of heat treating the precursor mixture, and a third step of sintering the heat treated precursor mixture to produce a LMO. x and a third step of manufacturing a positive electrode active material, thereby seeking to solve the above-mentioned problems.
[0033] As a result, the present invention can induce particle growth due to a uniform reaction of primary particles within secondary particles constituting a positive electrode active material, thereby controlling nanoscale defects and solving the problem of performance degradation over a long lifespan. It is also possible to easily synthesize a positive electrode active material having high capacity in a single synthesis process, with the stability being guaranteed without the need for special additives, and the application to various industries in which lithium secondary batteries are used can be greatly improved.
[0034] The present invention will now be described in detail with reference to the drawings.
[0035] [Method of manufacturing positive electrode active material] In the method for preparing a positive electrode active material according to the present invention, the first step is to mix a metal hydroxide and a lithium precursor to form a precursor mixture, and the second step is to heat-treat the precursor mixture.
[0036] Generally, the positive electrode active material used in lithium secondary batteries has a secondary particle structure of several μm in size, which is formed by agglomeration of fine primary particles of submicron size, and the positive electrode active material with the secondary particle structure has a problem that the primary particles that have aggregated during repeated charging and discharging are separated, causing the secondary particles to break and deteriorating the battery characteristics. This problem is caused by the structural characteristics of the secondary particles, and in particular, the positive electrode active material has the advantage of reducing costs by replacing a part of expensive cobalt with nickel, having high energy density and relatively long life, and being able to increase the reversible capacity of lithium secondary batteries. In the case of Ni-based layered positive electrode active materials, there is a problem of the formation of atomic-scale defects such as oxygen generation and cation mixing, and when atomic-scale defects and nano-level defects such as nanopores occur, they exist in various sizes, from voids within particles to voids between particles, causing deterioration of life characteristics.
[0037] More specifically, referring to FIG. 1, a cross section of secondary particles after 150 cycles for a conventional Ni-based layered positive electrode active material was observed, and it was confirmed that sudden cracks of the secondary particles were observed due to the infiltration of electrolytes between the giant pores generated during the synthesis process and the uneven contraction / expansion during the charge / discharge process. As a result, measures to suppress the formation of atomic and nano defects have been mentioned. For example, various methods have been reported to design synthesis conditions that control the synthesis temperature, pretreatment time, lithium content, etc., as an attempt to synthesize a positive electrode active material with a stable atomic structure by doping with various dopants (Al, B, Zr, Nb, Ta, etc.) or as a method to suppress defects formed during the synthesis process. However, such existing research focuses on the control of atomic unit defects, and the correlation between various scale defects and a method to suppress them have never been introduced.
[0038] Thus, the present invention can solve the above-mentioned problem of performance deterioration over a long life that appears in a positive electrode active material in the form of secondary particles by inducing particle growth due to uniform reaction of primary particles in secondary particles and controlling nanoscale defects by carrying out pretreatment of the precursor mixture prepared in the first step at a temperature at which the precursor mixture starts to react in the second step and then performing final synthesis. That is, referring to FIG. 2, it can be seen that when the pretreatment in the second step according to the present invention described below is performed, secondary particles are well maintained, and the formation of intraparticle pores during the synthesis process can be minimized, and atomic defects and nano defects can be minimized.
[0039] To this end, the present invention first clarifies the temperature at which a precursor mixture that can cause a sudden change in atomic defects that lead to nano-defects begins to react and an intermediate phase is formed, and then it is confirmed that forming a sufficiently uniform intermediate phase at this temperature can suppress sudden changes on an atomic scale.
[0040] More specifically, referring to FIG. 3, thermogravimetric analysis (TGA) shows that the precursor mixture undergoes the greatest weight loss from about 200° C. to 250° C., and a relatively small weight loss from about 250° C. to 400° C., with the reaction beginning to occur at about 200° C.
[0041] Also, referring to FIG. 4a, when comparing the phase fractions of the product by Rietveld analysis of the X-ray diffraction (XRD) pattern, it can be seen that the precursor mixture exists immediately after reaching 250°C from room temperature, whereas when sintering at 250°C for 6 hours, all the precursor mixture is decomposed and about 80wt.% or more of intermediate phase is formed. As a result, it can be seen that the reaction of the precursor mixture starts to occur at 250°C, as in the TGA result. Also, referring to FIG. 4b, the Rietveld analysis of the neutron diffraction (ND) pattern shows that the composition of the intermediate product is Li x TM 2-x It can be seen that it is O2(x=~0.4).
[0042] 5 and 6, it can be seen that the precursor mixture starts reacting immediately after reaching 250° C. without primary sintering, and most of the reaction is completed at 400° C. as all transition metal precursors are decomposed. Also, it can be seen that the change in lattice constant to the c-axis is mitigated when the precursor mixture is synthesized up to the synthesis temperature of 780° C. after primary sintering at 250° C. for 6 hours, unlike when the precursor mixture is synthesized up to the synthesis temperature of 780° C. without primary sintering, and therefore it can be seen that the formation of a sufficiently uniform intermediate phase at 250° C., where the reaction occurs, can suppress sudden changes on an atomic scale.
[0043] Considering these results, it can be seen that the intermediate phase represented by Chemical Formula 2 below is formed in an amount of 40 to 80 wt % based on the total weight of the precursor mixture through the second heat treatment, and uniform growth of primary particles within secondary particles is induced. [ka] In this case, M is one or more selected from Co (cobalt), Ni (nickel), Al (aluminum), Mn (manganese) and Mg (magnesium), and x is a constant of 0.2 to 0.8.
[0044] More specifically, referring to FIG. 7, a comparison of the bulk and surface oxidation numbers of an intermediate phase sample sintered at 250°C for 6 hours and an intermediate phase sample sintered immediately after 400°C, which have the same phase fraction, shows that the bulk oxidation numbers of the two samples are the same, but the surface oxidation number of the 400°C sample has a higher photon energy at the Ni L3-edge than the sample sintered at 250°C for 6 hours. Similarly, referring to FIG. 8, XANES analysis and transmission electron microscope analysis show that the distribution of Ni oxidation numbers of secondary particles between the sample sintered immediately after 400°C for 6 hours and the sample sintered immediately after 400°C shows that the Ni oxidation number of the sample sintered immediately after 400°C increases from the core to the surface, whereas the sample sintered at 250°C for 6 hours has a uniform Ni oxidation number overall.
[0045] In this way, the present invention can control nanoscale defects by performing the pretreatment at a temperature where the precursor mixture starts to react and then performing the final synthesis, thereby inducing particle growth due to uniform reaction of primary particles in secondary particles. For this purpose, the pretreatment of the second step can be performed on the precursor mixture prepared in the first step at 200-400°C for 2-8 hours, more preferably at 230-350°C for 2-6 hours. In this case, when the temperature for performing the second step is less than 200°C, Li x M 2-x If the second step is performed at a temperature of more than 400°C, the atomic defects may change rapidly during the sintering process, resulting in the formation of nano-defects. If the second step is performed for less than 2 hours, the Li x M 2-x If the formation of the O2 intermediate phase is less than 50 wt.%, there may be a problem that the effect of controlling nano-defects is reduced. Also, if the execution time of the second step exceeds 8 hours, it may be disadvantageous in terms of process operation.
[0046] In this case, the metal hydroxide of the precursor mixture may be one or more compounds selected from the oxides or hydroxides of Ni, Co, Mn, Al, Mg, and V as a transition metal source, and the lithium precursor of the precursor mixture may be, but is not limited to, LiOH, LiOH·H2O, or Li2CO3, and various lithium-containing compounds capable of supplying lithium element may be used.
[0047] According to an embodiment of the present invention, the metal hydroxide and the lithium precursor may be mixed in a molar ratio of 1:0.9 to 1.1. In this case, if the molar ratio of the metal hydroxide and the lithium precursor is less than 1:0.9, NiO having a rock salt structure is formed in the positive electrode active material, which may cause a problem of deteriorating electrochemical performance, and if the molar ratio of the metal hydroxide and the lithium precursor is more than 1:1.1, there may be a problem of forming a large amount of residual lithium compounds such as Li2CO3 and LiOH.
[0048] In addition, in the present invention, in order to induce a more uniform synthesis of the primary particles within the secondary particles, the lithium precursor may further contain a molten salt, and the first and second steps described above may be carried out.
[0049] More specifically, referring to Fig. 9, the lithium precursor further includes a molten salt, and through the results of comparing the phase fractions of the product by analyzing the XRD and ND patterns during the synthesis process of the precursor mixture, it can be seen that the use of the molten salt has a lower melting point than the use of LiOH alone, so the reaction begins at 200°C, which is lower than the use of LiOH alone, and as a result, after sintering at 200°C for 6 hours, all of the precursor mixture is decomposed and about 80% of the intermediate phase is formed. This indicates that faster lithiation is induced than in the existing solid-phase synthesis using only LiOH, and that fast lithium diffusion is possible in the synthesis process.
[0050] 10, it can be seen that secondary particles having high density and close to zero pores are formed when the lithium precursor is further added with molten salt by comparing the cross sections of the final synthesized secondary particles when the lithium precursor is further added with molten salt. This shows that when the lithium precursor is further added with molten salt to synthesize the positive electrode active material, the positive electrode active material having close to zero nano defects can be manufactured.
[0051] For this purpose, the molten salt may be at least one selected from the group consisting of LiNO3, Li2SO4, Li2CO3, LiCl, LiI, and LiBr, and more preferably LiNO3 or Li2SO4. In this case, before the transition metal compound is decomposed by releasing gas, Li containing a large amount of lithium is decomposed. x M 2-x It can be more advantageous to effectively generate the O2(x>0.6) intermediate phase at a lower temperature and reduce the formation of nanodefects during the sintering process.
[0052] Further, the lithium precursor may be mixed with either LiOH or LiOH·H2O and the molten salt at a ratio of 1:0.5 to 2, more preferably at a molar ratio of 1:0.9 to 1.05. At this time, if the lithium precursor and the molten salt are mixed at a molar ratio of less than 1:0.5 or more than 1:2, there may be a problem that the eutectic temperature of the molten salt is exceeded and a higher secondary sintering temperature is required.
[0053] Next, in the third step of the method for producing a positive electrode active material according to the present invention, the heat-treated precursor mixture is sintered to produce LMO x wherein L is Li (lithium), M is one or more selected from Co (cobalt), Ni (nickel), Al (aluminum), Mn (manganese) and Mg (magnesium), and x is a constant of 0.5 to 2.5.
[0054] The third step can use known ordinary methods and conditions for sintering the precursor mixture that has undergone the first and second steps to produce a positive electrode active material, and is not particularly limited. Preferably, the third step is carried out at 600 to 900 °C for 6 to 16 hours to produce the final positive electrode active material.
[0055] According to such a preferred embodiment, the LMO x can obtain a compound represented by the following Chemical Formula 1.
Chemical Formula
[0056] In this case, if the temperature for performing the third step is less than 600°C, as seen in Figure 5, a pseudo-layered phase in which lithium and transition metal are partially arranged in a disordered manner may be formed, instead of a layered positive electrode material in which the lithium layer and the transition metal layer are separated and synthesized, and if the temperature for performing the third step is more than 900°C, a NiO phase with a rock salt structure may be formed. If the time for performing the third step is less than 4 hours, lithium and transition metal in the crystal structure may be partially arranged in a disordered manner between layers, and if the time for performing the third step is more than 16 hours, lithium may be sublimated, resulting in the synthesis of a crystal structure in which some lithium is deficient.
[0057] [Cathode active material] Next, the cathode active material according to the present invention will be described, except that, to avoid duplication, a description of the same technical concept as in the above-mentioned method for manufacturing the cathode active material will be omitted.
[0058] The positive electrode active material according to the present invention is a positive electrode active material in the form of secondary particles in which atomic unit and nanoscale defects are minimized, and may be represented by the following Chemical Formula 3, or according to a more preferred embodiment, may be a compound represented by the following Chemical Formula 4. [ka] In this case, L is Li (lithium), M is one or more selected from Co (cobalt), Ni (nickel), Al (aluminum), Mn (manganese) and Mg (magnesium), and x is a constant of 0.5 to 2.5. [ka]
[0059] In this regard, the present invention aims to control nanoscale defects by inducing particle growth due to uniform reaction of primary particles within secondary particles by performing pretreatment at a temperature at which a metal hydroxide and a lithium precursor start to react, followed by final synthesis, and the cathode active material may include first voids formed between particles having a mean radius of less than 960 Å and second voids formed within particles having a mean radius of less than 80 Å.
[0060] More specifically, the secondary voids formed within the particles may preferably have an average radius of less than 80 Å, more preferably less than 75 Å, and most preferably less than 70 Å.
[0061] In this regard, the first void (macropore) means a void (pore) formed between particles and having a radius of 500 Å or more, the second void (mesopore) means a void formed within a particle and having a radius of 50 to 500 Å, and the third void (micropore) means a void formed within a particle and having a radius of 50 Å or less.
[0062] During sintering, micropores are formed due to the separation of precursors as a result of reactions. At this time, as the sintering temperature gradually increases, the micropores diffuse and combine to form mesopores. At this time, the micropores and mesopores are mainly present inside the primary particles. As the sintering temperature increases further, some of the micropores and mesopores that were present inside the primary particles move to the surface of the particles and combine, and the pores formed on the surface by this movement combine with the pores on the surface of the adjacent particles to form macropores as pores between the particles.
[0063] In this case, since micropores and mesopores exist inside the particles, they can act as nano-unit defects in the primary particles. The presence of such defects leads to further exposure of the interface and side reactions with the electrolyte, which ultimately leads to deterioration of the battery's lifespan. Therefore, the smaller the average radius and distribution value of the pores in micropores and mesopores, the more advantageous it is in maintaining the battery's lifespan and preventing deterioration. Therefore, if the average radius of the second pores corresponding to mesopores is 80 Å or more, it can be disadvantageous in terms of battery performance, such as a rapid decrease in battery capacity due to a high defect level. In addition, the distribution of the second pores is also 0.0009 cm 3 For the same reason, a distribution of 0.1 to 1.0 μm / g or more can be disadvantageous in terms of battery performance.
[0064] In the case of macropores, when the positive electrode active material contains less than a certain level of macropores as voids between particles, it can provide a buffering effect during battery operation, which can be advantageous in terms of battery performance, but when the positive electrode active material contains more than a certain level, it can be disadvantageous in terms of battery performance. As a result, when the average radius of the first pores is 960 Å or more, it can be disadvantageous in terms of battery performance, such as a rapid decrease in battery capacity due to a high defect level. In addition, when the distribution of the first pores is less than 0.013 cm 3 / g or more, it may be disadvantageous in terms of battery performance, such as a rapid decrease in battery capacity, for the same reason. However, when the distribution of the first voids is 0.013 cm 3 / g, the more even the distribution is, the more important factor is how even the distribution is, rather than the distribution value. The more even the distribution is, the less the risk of collapse is from a structural standpoint, and the more stable the buffer effect can be exhibited, which is advantageous in terms of battery performance.
[0065] More specifically, referring to FIG. 11, it was confirmed that without primary sintering, a rapid lattice structure change and a non-uniform reaction were induced during synthesis, many defects of several hundred nanometers were formed at the center of the core, and the rapid lattice change occurring at the atomic scale could lead to nanoscale defects. Also, it can be seen that forming a uniform intermediate phase can suppress rapid changes not only at the atomic scale but also at the nanoscale.
[0066] Referring to FIGS. 12 to 14 in which the size and distribution changes of the first, second, and third voids were comparatively analyzed, it was found that the macropores decreased as the synthesis temperature increased due to the primary particles that gradually grew during synthesis. Also, the distribution of the second and third voids showed that the most pores were observed at 400 °C where micropores began to form and the reaction occurred rapidly after the reaction started at 300 °C. Here, it can be seen that the rapid increase in micropores was induced by the rapid reaction. Also, from 500 °C, the macropores increased due to the combination of mesopores, which is consistent with the observation of many large pores in the particle cross-section SEM image of FIG. 10 as described above. At this time, FIGS. 12 to 13 show the results of measuring the particle size distribution during the process of synthesizing the cathode active material without primary sintering.
[0067] Also, through the structural analysis results of FIGS. 15 to 19, when synthesized without primary sintering and when synthesized after primary sintering at 200 to 400 °C, when synthesized without primary sintering, many macropores and mesopores of the largest size were observed, pores inside and between particles were observed, and non-uniformly distributed pores aggregated to locally form large pores. In contrast, when synthesized after primary sintering, macropores and mesopores of the smallest size and few in number were observed, and it can be seen that the pores between small particles uniformly spread to form high-density secondary particles. This means that when proceeding with low-temperature primary sintering during the synthesis process, a slow and uniform reaction is induced, and Li x M 2-x The formation of the O2(0.2 < x < 0.8) intermediate phase is uniform, and the formation of uniform pores of small size leads to the final synthesis.
[0068] As described above, the present invention can induce particle growth due to a uniform reaction of primary particles within secondary particles constituting a positive electrode active material, thereby controlling nanoscale defects, thereby solving the problem of performance degradation over a long life span, and can easily synthesize a positive electrode active material having high capacity in a single synthesis process while ensuring stability without the need for special additives, thereby greatly improving the applicability of lithium secondary batteries including the positive electrode active material according to the present invention to various industrial groups.
[0069] Hereinafter, the present invention will be described in more detail with reference to examples. However, it should be understood that the following examples are not intended to limit the scope of the present invention, but are intended to aid in the understanding of the present invention.
[0070] [Example 1: Production of positive electrode active material] In order to prepare the positive electrode active material according to the present invention, Ni 0.92 Co 0.03 Mn 0.05 A (OH)2+LiOH·H2O precursor mixture sample was prepared. The precursor mixture was synthesized at a transition metal compound:lithium compound molar ratio of 1:1-1.03, in a gas atmosphere of 400-500mL / min O2, and at a final synthesis temperature of 780°C. After primary sintering at 200°C for 6 hours, secondary sintering was carried out at 780°C for 12 hours to obtain the final positive electrode active material LiNi 0.92 Co 0.03 Mn 0.05 O2 was synthesized.
[0071] [Examples 2 to 4: Production of positive electrode active material] The positive electrode active materials were prepared in the same manner as in Example 1, but at different primary sintering temperatures as shown in Table 1 below.
[0072] [Example 5: Production of positive electrode active material] Ni 0.92 Co 0.03 Mn 0.05(OH)2 + LiOH·H2O:LiNO3 or Li2SO4 (in a ratio of 2:3) A precursor mixture sample was used, and it was produced in the same manner as Example 1 except that the primary sintering temperature was varied as shown in Table 1 below.
[0073] [Comparative Example 1: Production of Cathode Active Material] The cathode active material was produced in the same manner as Example 1 without proceeding with the primary sintering as shown in Table 1 below.
Table 1
[0074] [Experimental Example 1: Thermogravimetric Analysis] As shown in Figure 3, thermogravimetric analysis (TGA) was carried out to set the primary sintering temperature for uniform synthesis. As a result, it was confirmed that the precursor mixture had the largest weight reduction from about 200°C to 250°C and a relatively small weight reduction from about 250°C to 400°C, and the reaction began to occur from about 200°C.
[0075] [Experimental Example 2: Rietveld Analysis of X-ray Diffraction (XRD) Pattern] Referring to Figure 4a, the X-ray diffraction (XRD) pattern during the synthesis process of the precursor mixture was subjected to Rietveld analysis to compare the phase fractions of the products. From room temperature to 250°C, only Ni 0.92 Co 0.03 Mn 0.05 (OH)2 and LiOH were present, while after sintering at 250°C for 6 hours, all Ni 0.92 Co 0.03 Mn 0.05 (OH)2 was decomposed, and it was confirmed that an Li x M 2-x O2 (0.2 < x < 0.8) R-3m intermediate phase was formed. Immediately after reaching 300°C, the precursor mixture had already partially reacted, and about 30wt.% of Li x M 2-xO₂(0.2 < x < 0.8) was formed, and after sintering at 300 °C for 6 hours, a phase fraction similar to that sintered at 250 °C for 6 hours was confirmed. It was confirmed that all the transition metal precursors were decomposed immediately after reaching 400 °C, and as a result, similar to the TGA results, it indicates that the reaction of the precursor mixture begins to occur from 250 °C.
[0076] [Experimental Example 3: Rietveld Analysis of Neutron Diffraction Pattern] Referring to Fig. 4b, in order to quantify the lithium content of the intermediate product, the neutron diffraction patterns of the intermediate phase sintered at 250 °C for 6 hours and the 400 °C intermediate phase with the same phase fraction were analyzed through the Rietveld analysis method. As a result, it was found that both phases have an R-3m layered bulk structure of Li x M 2-x O₂(x = ~0.4).
[0077] [Experimental Example 4: Analysis of Phase Fraction of Intermediate Product] Referring to Fig. 5, by analyzing the X-ray diffraction (XRD) pattern during the real-time synthesis process of the precursor mixture, it was also confirmed that the precursor mixture began to react immediately after reaching 250 °C without primary sintering, and all the transition metal precursors were decomposed at 400 °C, and most of the reactions were completed.
[0078] [Experimental Example 5: Analysis of Phase Fraction and Lattice Constant Change during Primary Sintering] As shown in Fig. 6, the XRD pattern during the real-time primary sintering at a reaction temperature of 250 °C was further analyzed. All the transition metal precursors were decomposed after sintering at 250 °C for 3 hours. Different from synthesizing to a synthesis temperature of 780 °C without primary sintering, when synthesizing to a synthesis temperature of 780 °C after primary sintering at 250 °C for 6 hours, it was further confirmed that the change in the lattice constant along the c-axis was alleviated. This means that forming a sufficiently uniform Li x M 2-x O₂(0.2 < x < 0.8) intermediate phase at 250 °C, where the reaction occurs, can suppress rapid changes at the atomic scale.
[0079] [Experimental Example 6: XAS Analysis] Referring to Fig. 7, in order to confirm the particle growth uniformity of the secondary particles before and after the primary sintering, the oxidation numbers of the bulk and surface of the 250 °C sintered intermediate phase sample and the 400 °C immediately after intermediate phase sample with the same phase fraction were compared through hard and soft X-ray absorption spectroscopy (XAS) analysis. As a result, it was confirmed that the bulk oxidation numbers of the two samples were the same, but the surface oxidation number had a higher photon energy at the Ni L3-edge of the 400 °C sample and had a higher surface oxidation number than the sample sintered at 250 °C for 6 hours.
[0080] [Experimental Example 7: XANES Analysis and Transmission Electron Microscopy Analysis] Referring to Fig. 8, the Ni oxidation number distribution of the secondary particles between the sample sintered at 250 °C for 6 hours and the 400 °C immediately after sample was also confirmed through transmission X-ray microscopy (TXM)-X-ray absorption near edge structure (XANES) analysis and transmission electron microscopy (TEM)-electron energy loss spectroscopy (EELS) analysis. As can be seen from the drawings, the 400 °C immediately after sample shows that the oxidation number of Ni increases from the core to the surface, while the sample sintered at 250 °C for 6 hours has an overall uniform Ni oxidation number.
[0081] [Experimental Example 8: SEM Cross-Section Analysis] Referring to Fig. 11, in the 400 °C intermediate phase without primary sintering, a large number of macropores were observed towards the inside of the secondary particles, while the cross-section of the secondary particles of the intermediate phase primary sintered at 250 °C was very uniform. This indicates that the rapid lattice structure change and non-uniform reaction during synthesis were induced without primary sintering, and many defects of several hundred nanometers were formed at the center of the core, confirming that the rapid lattice change occurring at the atomic scale observed in the above diffraction analysis can lead to nanoscale defects. Also, it was shown that forming a uniform Li x M 2-x O2 (0.2 < x < 0.8) intermediate phase can suppress rapid changes not only at the atomic scale but also at the nanoscale.
[0082] [Experimental Example 9: SAXS and SANS Analysis] Referring to Figures 12 to 14, the average nano-sized pore size and distribution change of secondary particles were compared and analyzed for the first time using small angle X-ray scattering and small angle neutron scattering (SAXS and SANS) analysis methods to quantitatively analyze the nanopores of secondary particles generated during the synthesis process. Here, Figures 12 to 13 show the results of measuring the particle size distribution in the process of synthesizing a cathode active material without primary sintering. From room temperature to 500°C, the micropore size increased due to the reaction of the precursor mixture, and from 600°C to 780°C, the mesopore size increased due to the merging of the micropores. The macropores decreased as the synthesis temperature increased due to the primary particles that gradually grew during the synthesis. In addition, the pore distribution shows that micropores begin to form at 300°C after the reaction has started, and the most pores are observed at 400°C, where the reaction occurs rapidly. Here, the sudden increase in macropores is induced by the sudden reaction, which coincides with the fact that many large pores are observed in the 400°C particle cross-section SEM image in Figure 8. In addition, it was confirmed that from 500°C, the number of macropores increases due to the combination of mesopores. When comparing the particle distribution of the sample immediately after 400°C, where the largest micropores are formed, and the sample sintered at 250°C for 6 hours, which is similar, it was confirmed that the sample sintered at 250°C for 6 hours had a smaller and more uniform micropore distribution. This indicates that the overall reaction level of the two samples is similar, but the process of heat treatment at a low temperature can induce a uniform reaction within the secondary particles.
[0083] [Experimental Example 10: Radius and content distribution of first and second voids in positive electrode active material] Tables 2 and 3 below show the radius and content distribution of the first and second voids of the positive electrode active material prepared without primary sintering and the positive electrode active material prepared with primary sintering.
[0084] [Table 2] [Table 3]
[0085] [Experimental Example 11: Analyzing SEM Cross-Section, XRD, and ND Patterns] Referring to FIGS. 15 to 19, the comparison between the sample finally synthesized without primary sintering and the final-phase sample primary-sintered at 200 to 400° C. is shown in FIGS. 15 to 19. The analysis of the bulk structure through XRD and ND analysis was similar for all samples, but the pore quantification analysis through SAXS / SANS analysis showed differences. For the sample (P-NCM) synthesized without primary sintering, many macro and mesopores of the largest size were observed, while for the sample (P250-NCM) synthesized after primary sintering at 250° C., few macro and mesopores of the smallest size were observed. This means that when proceeding with low-temperature primary sintering during the synthesis process, a slow and uniform reaction is induced, leading to the uniform formation of the Li x M 2-x O2 (0.2 < x < 0.8) intermediate phase and the formation of uniform pores of small size up to the final synthesis. To confirm the information on pores obtained through SAXS / SANS analysis, the TEM and SEM cross-sections of the representative samples P-NCM and P250-NCM were compared. For P-NCM, pores inside and between particles were observed, and aggregated large pores were locally observed with unevenly distributed pores, while for P250-NCM, it was confirmed that pores between small particles were uniformly spread to form high-density secondary particles, which is consistent with the SAXS / SANS analysis results.
[0086] [Experimental Example 12: Comparison of Electrochemical Performance] Referring to FIG. 20, the electrochemical performance of the sample directly synthesized without primary sintering and the sample primary-sintered at 200 to 400° C. was compared. It was confirmed that the electrochemical cycle characteristics of all the primary-sintered samples except P-NCM were improved, and among them, the electrochemical characteristics (cycle and capacity) of P250-NCM, which was synthesized most uniformly, were improved the most.
[0087] [Experimental Example 13: Analyzing SEM, XRD, and ND Patterns for Example 5] Referring to FIGS. 9 and 10, the XRD and ND patterns during the synthesis process of the eutectic precursor mixture were analyzed to compare the phase fractions of the products. When using eutectic molten salt, since it has a lower melting point than when only using existing LiOH, the reaction starts at a lower 200 °C than before. As a result, after sintering at 200 °C for 6 hours, all Ni 0.92 Co 0.03 Mn 0.05 (OH)2 is decomposed, and it was confirmed that about 80% of Li x M 2-x O2 (0.6 < x < 0.8) is formed. This indicates that it induces faster lithiation of the matrix phase than the solid-phase synthesis using only existing LiOH, and fast lithium diffusion in the eutectic synthesis process was confirmed. The cross-sections of the final synthesized secondary particles were compared when using the existing lithium precursor LiOH and when using eutectic molten salt. As a result, it was confirmed that PE200-NCM synthesized in the eutectic process has secondary particles with the highest density and close to zero pores. This indicates that the eutectic synthesis process is closest to a method for synthesizing a cathode active material with near-zero nanodefects.
[0088] [Experimental Example 14: Comparison of Electrochemical Performance with Respect to Example 5] Referring to FIGS. 21 and 22, the electrochemical cycle characteristics of three samples were compared. As shown in the left figure, there is no decrease in cycle characteristics up to 50 cycles based on the 0.15C-rate, and it showed improved characteristics in the long-term life characteristics of 200 cycles compared to the samples (P-NCM, P250-NCM) using the existing lithium precursor LiOH. Also, as a result of observing the cross-section of the secondary particles after 150 cycles, for P-NCM synthesized by the existing synthesis process, electrolyte penetration was observed between the macropores generated during the synthesis process, and rapid cracking of the secondary particles was observed due to non-uniform shrinkage / expansion during charge and discharge processes. In contrast, for P250-NCM synthesized after primary sintering and PE200-NCM synthesized by the eutectic process, it was confirmed that the secondary particles were well maintained as they were at first, demonstrating that minimizing the formation of pores inside the particles during the synthesis process is an important factor for the synthesis of stable cathode active materials.
Claims
1. A first step of mixing a metal hydroxide and a lithium precursor to form a precursor mixture; a second step of heat treating the precursor mixture; and The heat-treated precursor mixture is sintered to form an LMO. x A third step of producing a positive electrode active material. In this case, L is Li (lithium), M is one or more selected from Co (cobalt), Ni (nickel), Al (aluminum), Mn (manganese) and Mg (magnesium), and x is a constant of 0.5 to 2.
5.
2. The LMO x The method for producing a positive electrode active material according to claim 1, characterized in that is a compound represented by the following Chemical Formula 1. [Formula 1] In this case, the constants are 0.8≦a<1.0, 0<b<0.1, and 0<c<0.
1.
3. The method of claim 1 , wherein the lithium precursor in the first step further comprises a molten salt.
4. 2. The method of claim 1, wherein an intermediate phase represented by Chemical Formula 2 below is formed by the second heat treatment, and uniform growth of primary particles in secondary particles is induced. [Case 2] In this case, M is one or more selected from Co (cobalt), Ni (nickel), Al (aluminum), Mn (manganese) and Mg (magnesium), and x is a constant of 0.2 to 0.
8.
5. 2. The method of claim 1, wherein the second heat treatment is performed at 200 to 400° C. for 2 to 8 hours.
6. 2. The method of claim 1, wherein the second heat treatment is performed at 230 to 350° C. for 2 to 6 hours.
7. 2. The method of claim 1, wherein the metal hydroxide and the lithium precursor in the first step are mixed in a molar ratio of 1:0.9 to 1.
1.
8. 2. The method of claim 1, wherein the third step is performed at 600 to 900° C. for 4 to 16 hours.
9. The molten salt is LiNO 3 , Li 2 SO 4 , Li 2 CO 3 , LiCl, LiI and LiBr, and the lithium precursor is LiOH or LiOH.H 2 4. The method for producing a positive electrode active material according to claim 3, wherein any one of O and the molten salt is mixed in a molar ratio of 1:0.5 to 2.
10. 5. The method of claim 4, wherein the intermediate phase is contained in an amount of 40 to 80 wt % based on the total weight of the precursor mixture.
11. The positive electrode active material is a secondary particle type positive electrode active material in which atomic and nano-scale defects are minimized, and is represented by the following formula 3: First voids formed between particles having a mean radius of less than 960 Å; and a second void formed within the particle having a mean radius of less than 80 Å. [C3] In this case, L is Li (lithium), M is one or more selected from Co (cobalt), Ni (nickel), Al (aluminum), Mn (manganese) and Mg (magnesium), and x is a constant of 0.5 to 2.
5.
12. The positive electrode active material according to claim 11, characterized in that the positive electrode active material is a compound represented by the following Chemical Formula 4. [C4] In this case, the constants are 0.8≦a<1.0, 0<b<0.1, and 0<c<0.
1.
13. The first gap is 0.013 cm 3 / g, and the second gap has a distribution of less than 0.0009 cm 3 The positive electrode active material according to claim 11, characterized in that it has a distribution of less than / g.
14. The second gap is 0.0007 cm 3 The positive electrode active material according to claim 13, characterized in that it has a distribution of less than / g.
15. A lithium secondary battery comprising the positive electrode active material according to claim 11.
Citation Information
Patent Citations
Method for preparing high-nickel cathode material for lithium secondary battery
CN110137488A
Method for producing lithium metal phosphate
JP2017538652A
Nickel-based active material for lithium secondary battery, method of preparing the same, and lithium secondary battery including positive electrode including the same
JP2018014326A
Positive electrode active material for lithium secondary battery, positive electrode for lithium secondary battery and lithium secondary battery
JP2018174106A
Precursors and methods for preparing Ni-based Li-transition metal oxide cathodes for rechargeable batteries
JP2018529195A
